GESTÃO DA CULTURA NA UNIVERSIDADE: O NÚCLEO DE ARTE E CULTURA DA UNIVERSIDADE METODISTA DE SÃO PAULO - SILVA, Claudia Cezar da (2016)
This dissertation results from an autobiographical reflection, based on the researcher ´s recovery of memories and experiences during the life-work journey while managing the Center for Art and Culture (NAC) of the Methodist University of São Paulo (UMESP ), since its inception in 2005. Understanding the process of creation, formation and inclusion of NAC at UMESP, as well as the exercise of cultural management in this university space were goals of this research, which highlights the dialogue between education and culture, mediated by art, from the insertion of artistic and cultural activities focused on respect for differences and appreciation of human and cultural diversity. What is the role of the cultural action within a university? How these actions can add to the process of educational training? What were the challenges involved the construction and establishment of the Center for Art and Culture at UMESP? These were generating issues for the development of this work, which used an (auto) biographical methodology. In the narrative, the researcher sought to revisit and reframe, with a view to producing knowledge, memories and stories that contributed to the construction of her own identity and that boosted her integration in the management of culture at UMESP, legitimizing and firming the Center for Art and Culture´s action, over its 10 years of existence. In reflecting on this practice, it became clear that working with the subjectivities is the great challenge of managing culture, as well as the construction of collaborative processes, in the perspective of "cause" and not "doing for" is the way to strengthening and deepening the actions.